MÉTODOS DE DESINFESTAÇÃO NO ISOLAMENTO E INDUÇÃO IN VITRO DE CLONES DE ERVA-MATE - Prado, Débora Cristina Pereira (2018)
Ilex paraguariensis (mate) is a species of significant environmental, social and economic importance in the southern region of Brazil. Methods of vegetative propagation, such as in vitro cultivation, provided that viable protocols are developed, can be used for the production of plantlets from selected clones, to form mate plantations with better uniformity. However, bacterial and fungal contamination and phenolic oxidation has been the major obstacle for an in vitro propagation of mate. The objective of this work was to evaluate the effect of chemical and organic solutions in different immersion times (10, 20, 30 and 40 minutes) in the isolation and in vitro induction of axillary buds in nodal segments and isolated axillary buds. A chemical solution used in the experiments consisted of sodium hypochlorite (NaOCl) (7.5, 10 and 20 mL.L-1), and as organic solutions were Equisetum hyemale L. (10 gL-1), propolis 5 and 10 mL.L-1), essential oils of Melaleuca alternifolia Cheel (melaleuca) (5 and 10 mL.L-1), Menta arvensis L. (Mint) (1.25; 2.5; 10 mL.L-1), Syzygium aromaticum (L.) Merr. And LM Perry (clove) (1.25 and 10 mL.L-1) and Cymbopogon citratus (DC) Stapf (lemon grass) (1.25, 2.5 and 5 mL.L-1) in different combinations or pure, according to each experiment. To the MS culture medium, 100% and 25% concentration of salts of the medium, plus 3% sucrose, 0.01% myoinositol and BAP, added or not the products for use composition of the organic solution. It was also evaluated the type of propagule used in the elaboration of the explants (nodal segment and caulinar apex). To the nodal segments, was evaluated the origin of the propagules, as well as to the position of explant at budding (basal, median or apical). It was also evaluated the effect of antioxidants (ascorbic acid, cysteine and actived charcoal); concentrations of the 6-benzylaminopurine growth regulator (BAP, 1 and 2 mg.L1) and wood vinegar; and culture conditions (darkroom, growth room with photoperiod of 16 hours and BOD). The design was completely randomized, with five replicates consisting of four test tubes containing one explant per tube. Was evaluated the percentage of bacterial contamination, fungal contamination, oxidation, survival and sprout induction. Statistical analysis was executed through the Kruskal-Wallis test (KW) and the means were compared by the Duncan test at the 5% error probability level. The essential oils of M. arvensis and S. aromaticum use in disinfectants solution was efficient in the reduction of fungal and bacterial contamination. When added in culture medium was effective in obtaining cultures free from fungal and bacterial contamination, however there was no budding of axillary buds. The disinfestation treatment that resulted in a greater number of budding explants was immersion of the explants for 30 minutes in NaOCl 7,5 mL.L-1 . The propagules of the basal region, regardless of shoot size (bigger or smaller than 15 cm), resulted in higher survival and induced sprouts. Nodal segment explants resulted in greater budding, while isolated axillary buds resulted in lower contamination. There was no significant difference between applied doses of BAP and there was no reduction of the oxidation by antioxidants used, but the ascorbic acid promoted a control of bacterial contamination. The best culture condition of the explants was in a growth room without pre-isolation in a darkroom. Oxidation was the most limiting factor for the success of in vitro isolation and induction for the clones studied.